Digitalisasi dan Pembangunan Sosial: Perspektif Sosiologi terhadap Transformasi Masyarakat di Era Teknologi - Willia Novi Aryani; Adelia Irma Artika; Agi Bara Firdaus; Ahmad Jazily; Andrilia Agustin; Dimas Retyo Alfaozi; Gabriel Al Fathurrazaq Rusdi; Sindi Fitri Maulidia; Sylfiana Hidayatun Nikmah; Tubagus Satria Jaya; Wahidah Zahra (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the role of digitalization in driving social development in Indonesia through the perspective of development sociology. Digitalization has become a major force transforming social structures, values, and interaction patterns in societies worldwide. The results show that digital technology contributes significantly to increased social participation, economic empowerment, and equitable access to information. However, on the other hand, challenges arise in the form of a digital divide between urban and rural communities that can deepen social inequality. In the context of development sociology, digitalization is not only viewed as a technological process, but also as a social phenomenon that influences the dynamics of community life. Therefore, digital-based development must be directed inclusively so that all levels of society receive equal benefits. The government, educational institutions, and the community need to synergize in strengthening digital literacy and maintaining socio-cultural values ​​amidst the current of technological globalization. With a fair and participatory approach, digitalization can be an important means of strengthening social solidarity and realizing shared prosperity.